JARAK KELAHIRAN TERHADAP STATUS GIZI BALITA DI WILAYAH KERJA PUSKESMAS MUARA FAJAR TAHUN 2016 - Nurul Hidayah (LLDIKTI Wilayah X, 2021)
Toddlers are the age group that most often suffer from nutritional problems. According to WHO the number of malnourished sufferers in the world reaches 104 million children and malnutrition is the cause of one third of all causes of child death worldwide. One of the factors that influence nutritional status is an intermediate factor, an environmental factor and a mother factor that includes the number of children under five and birth spacing. This study aims to determine the relationship between birth spacing and nutritional status of children under five in the working area of Muara Fajar Public Health Center in 2016. This type of research is quantitative with cross sectional design. The sampling technique used accidental sampling, the population in this study were all mothers who had toddlers totaling 221 people with a sample of 86 people. Data collection uses primary data with questionnaire sheets. The analysis used is univariate and bivariate with chi square test. The results obtained by the value of Pvalue = 0.00. From the research conducted it can be concluded that there is a relationship between birth spacing and the nutritional status of toddlers.